Friendship network composition and subjective wellbeing - Sefa Awaworyi Churchill; Russell Smyth (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
Using data from the UK Community Life Survey, we present the first study to examine the relationship between heterogeneity in one's friendship network and subjective wellbeing. We measure network heterogeneity by the extent to which one's friends are similar to oneself with regard to ethnicity and religion. We find that people who have friendship networks with characteristics dissimilar to themselves have lower levels of subjective wellbeing. Specifically, our two-stage least squares (2SLS) estimates, using measures of ethnic and religious diversity based on the Herfindahl-type fractionalization index that are flipped between adjoining rural/urban areas as instruments, suggest that a standard deviation increase in the proportion of one's friends from different ethnic (religious) groups is associated with a decrease of 0.276 (0.451) standard deviations in subjective wellbeing.
Keywords: Z12; J15; I31; 330; friendship; heterogeneity; social capital; networks; wellbeing